Pemanfaatan Media Shopee Dalam Meningkatkan Penjualan Madu Masriana UMKM Di Iro Jaya - Kusumawardhany, Sayekti Indah; Putri, Ardelia Devi Eka; Fitriana, Annisa; Ariyani, Anisa Putri; Linuriyati, Annisa (Aktualisasi Pengabdian Masyarakat, 2024)
Historically, transactions were initially carried out directly or face to face, now they have changed to via the internet or online transactions. With the convenience of the internet, business people no longer experience difficulties in obtaining any information to support their business activities. E-commerce is a product marketing media with an electronic system that brings together many sellers and buyers who transact with each other. Currently, the growth of e-commerce is showing an increase because people's style is starting to slowly shift from initially shopping offline to tending to shop online. Therefore, it can be an opportunity for Madu Masriana MSME owners to participate in marketing their products in one of the e-commerce sites, namely Shopee, as an effort to increase sales of their products. Based on the explanation above, this research aims to utilize Shopee media to increase sales of Micro, Small and Medium Enterprises (MSMEs) at Madu Masriana. The method used in this service is the PAR (Participatory Action Research) method. The success rate of this discount technique increased by 5%. The increase figure is still relatively small because the evaluation period was only carried out for a short time, namely around 20 days. It is hoped that after this service, the use of sales on Shopee media can continue to increase.